1989
DOI: 10.1104/pp.91.2.500
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines as Modulators of Salt Tolerance in Rice Cultivars

Abstract: The effect of NaCI on the endogenous levels of diamine, putrescine and polyamines, spermidine and spermine, was studied in the shoot system of salt-tolerant and salt-sensitive lines of rice (Oryza sativa L.) cultivars during three growth stages. Salt stress increased the levels of diamine and polyamine in varying degrees among nine rice cultivars investigated. Salt tolerant AU 1, Co43, and CSC1 were effective in maintaining high concentrations of spermidine and spermine, while the content of putrescine was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
92
2
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(110 citation statements)
references
References 23 publications
15
92
2
1
Order By: Relevance
“…l), which is similar to the findings in rice, in which putrescine levels are not induced by salt stress (Krishnamurthy and Bhagwat, 1989). Conversely, putrescine biosynthesis was induced by many stresses, such as ozone (Langebartels et al, 1991;Scalet et al, 1995;Tuomainen et al, 1996), wounding (Yoza et al, 1996), osmotic stress (Flores and Galston, 1984), heat shock (Roy and Ghosh, 1996), oxygen deficiency (Reggiani et al, 1990), and K+ deficiency (Watson and Malmberg, 1996) in other species.…”
Section: Discussionsupporting
confidence: 83%
“…l), which is similar to the findings in rice, in which putrescine levels are not induced by salt stress (Krishnamurthy and Bhagwat, 1989). Conversely, putrescine biosynthesis was induced by many stresses, such as ozone (Langebartels et al, 1991;Scalet et al, 1995;Tuomainen et al, 1996), wounding (Yoza et al, 1996), osmotic stress (Flores and Galston, 1984), heat shock (Roy and Ghosh, 1996), oxygen deficiency (Reggiani et al, 1990), and K+ deficiency (Watson and Malmberg, 1996) in other species.…”
Section: Discussionsupporting
confidence: 83%
“…The role of PAs reported that salt-tolerant rice cultivars had higher level of Spd and Spm whereas salt sensitive cultivars maintained only a high level of Put (Basu & Ghosh 1991). Further measurement of PAs levels in different rice cultivars showed that sensitivity to salt stress in rice was associated with excessive accumulation of Put with low levels of Spd and Spm in the shoot systems of the salt sensitive cultivars under saline conditions (Krishnamurthy & Bhagwat 1989). It was inferred that tolerance to salinity in rice cultivars was due to high content of Spd and Spm and low level of Put.…”
Section: Salinitymentioning
confidence: 99%
“…NaC1-stressed rice (Ouyza sativa L.), for example, accumulates polyamines (Krishnamurthy and Bhagwat, 1989) and Pro (Chou et al, 1991;Alia and Saradhi, 1993). When administered externally, these molecules have been found to protect plants from some of the damage that is caused by drought or excess salinity (Kavi Kishor, 1989;Génard et al, 1991;Krishnamurthy, 1991).…”
mentioning
confidence: 99%